Sibling attachment inventory for senior secondary school students: standardization in Indian context - Guha, Sampurna; Beri, Nimisha (Intelektual Pustaka Media Utama, 2025)
The study aimed at exploring, confirming, and validating the factor structure of sibling attachment inventory (SAI) within the Indian cultural context. The hypothesis posits that SAI will show reliable sibling attachment measures, evaluating its psychometric properties with 250 students enrolled in Class XI within govt and private schools, selected through stratified random sampling across 10 districts of Delhi. The research unfolded in three phases: i) data collection utilizing original 25-item SAI; ii) data purification and analysis using SPSS version 23.0; and iii) verification of the factor structure through factor analysis employing principal component analysis (PCA) with varimax rotation and confirming the factor structure using AMOS. The results revealed inclusion of 23 items across three factors viz. trust, communication, and alienation, with high reliability coefficients (α) of 0.954, 0.786, and 0.621 respectively. Preliminary analysis demonstrated commendable internal consistency. This study highlights the importance of considering sibling relationships in understanding adolescent well-being, thereby addressing existing research gaps by focusing on sibling relationships among adolescents, an area often overlooked in favor of parental and peer dynamics. Thus, SAI can support the assessment of sibling-adolescent attachment, thereby helping to enhance intervention, and expanding attachment research scope beyond traditional family dynamics.